Pendekatan Fuzzy Logic dalam Perhitungan Harga Rental Truck Crane - Kurniawan, Avip; Irawan, Bei Harira; Prihadi, Deddy (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Calculating rental prices in the crane rental industry is essential in achieving competitiveness and optimal profits amidst increasingly tight business competition. Applying fuzzy logic, especially the Fuzzy Mamdani method, in calculating truck crane rental prices by Standard Operational Decision Procedures (SPOK) can significantly contribute to overcoming penetration and subjectivity that may be associated with factors that influence truck crane rental prices. The advantage of fuzzy logic, especially the Fuzzy Mamdani method, and its contribution to the crane rental industry lies in its ability to handle ambiguity in data and decision problems. The Fuzzy Mamdani method was chosen because of its high flexibility and ability to handle data tolerance values well. This research shows that applying fuzzy logic can help carry out optimal calculations to determine crane rental prices. Using input variables such as a distance of 40 km and a weight capacity of 25 tons, the calculation results show that the rental price is in the medium category. This reflects the synchronization of calculation results in determining crane rental prices, which can be adjusted to certain conditions and variables.